VALUE OF SPEED CAPABILITIES IN YOUTH SPEED CLIMBING AT HIGH SPORTS LEVEL - Krawczyk, Marcin; Pociecha, Mariusz; Ozimek, Mariusz; Stepek, Aleksandra; Kozioł, Paulina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Current research on speed climbing at the senior level shows that speed capabilities are a significant factor determining climbing time. The main purpose of our research was to evaluate the level of speed capabilities among young speed climbers and to examine the relationship between the level of speed capabilities and the results achieved during an international competition. The subjects of the research were girls and boys in the following age categories: Female Youth A (age=16.6), Female Youth B (age=14.5 years), Male Youth A (age=16.87 years) and Male Youth B (age=14.8 years). Measurements of somatic features were included: body height, body weight, percentage of fat tissue and BMI. Speed capabilities were measured with Wingate Test. The significance test of differences showed no significant differentiation within climbing times between the groups of girls and the groups of boys. A strong correlation between climbing time and relative peak power was noticed in the Female Youth B group. The correlation between peak power and climbing time was lower in the other groups. Research showed that in speed climbing, as career progresses, it is importance of other factors rather than speed capabilities that may increase. It can be assumed that with an increase in training experience, motor skills become more essential.